(untitled) (Global Journal of Science Frontier Research, 2014)
This study has evaluated the trends in investment, feeding and milk supply pattern on sample Dairy farms in Bikaner district of Rajasthan-the Arid zone (a typically Desert area). This study is based on the primary data which collected through personal interview method on prestructured and pretested schedule for the selection on dairy farms, a complete list of all dairy farms operating in Bikaner was obtained and five dairy farms having herd size of more than 20 milch animals were selected randomly for the year 2010-11. The data were analyzed by using various statistical measures like averages, ratios and percentage etc. to arrive the conclusions. Most of the dairy owners were facing the constraints for the lack of management practices adoption were non availability of green fodder, inadequate quantity, high cost of feed and fodder, dry fodder, salt and watering lack of space in Dairy farms, lack of awareness, Most of the dairy owners were practicing scientific management practices ie. Feeding of green fodder, cleaning of animals and animal shed and health practices, deworming and treatment were adopting fully and totting, dehorning, hoof treaming, artificial insemination and vaccination practice etc.